1995
DOI: 10.1029/94tc02547
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Euler pole for contemporary relative motion of Caribbean and North American plates using slip vectors of interplate earthquakes

Abstract: A number of different Euler poles have been proposed by various authors during the past 20 years to describe the relative motion of Caribbean (CA) and North American (NA) plates. These different solutions are a consequence of the small number of focal mechanism solutions of earthquakes, the short length of the plate boundaries of the Caribbean that consists of an active spreading center, the complicated and multibranched fault systems of several parts of the plate boundaries, and biases introduced in using sli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(70 citation statements)
references
References 34 publications
3
67
0
Order By: Relevance
“…The orientation of T min , the slower of the two P-wave measurements in transverse directions to the core axis, V pt1 and V pt2 , shows a clear correlation with presumed compressive stress. The direction of the maximum in situ stress in the accreted section is assumed to be parallel to the direction of the plate convergence vector (PCV) of 78° (Deng and Sykes, 1995). This assumption is based on AMS orientation data presented in Housen et al (1996), which are consistent with lateral shortening parallel to the PCV in the prism sediments above the décollement.…”
Section: Resultsmentioning
confidence: 52%
“…The orientation of T min , the slower of the two P-wave measurements in transverse directions to the core axis, V pt1 and V pt2 , shows a clear correlation with presumed compressive stress. The direction of the maximum in situ stress in the accreted section is assumed to be parallel to the direction of the plate convergence vector (PCV) of 78° (Deng and Sykes, 1995). This assumption is based on AMS orientation data presented in Housen et al (1996), which are consistent with lateral shortening parallel to the PCV in the prism sediments above the décollement.…”
Section: Resultsmentioning
confidence: 52%
“…The Panama Block has become partly coupled to the Nazca Plate, resulting in a Panama-Colombia collision that is presently occurring nearly twice as fast as Caribbean-South America relative motion; thus, the NW escape of the Panama slivers has ceased. corroborated by an updated assessment of circumCaribbean Plate boundary seismicity, which also indicated an 0708 azimuth of relative motion in the NE Caribbean (Deng & Sykes 1995). GPS positioning results (Dolan et al 1998;Perez et al 2001;Weber et al 2001) have confirmed the 20 mm/ annum rate and the 0708 and 0858 azimuths for the NE and SE Caribbean, respectively (Fig.…”
Section: Eocene -Middle Miocene Transcurrence and Oblique Collision Amentioning
confidence: 50%
“…Core physical properties and logging-while-drilling results also indicate the presence of high fluid pressures in two narrow intervals (505 and 514 mbsf) in the upper part of the décollement (Moore et al, 1995). The abrupt change in AMS orientations from horizontal-compression geometries to vertical-compaction geometries near the top of the décol-lement is thus most likely a manifestation of mechanical decoupling (Deng and Sykes, 1995).…”
Section: Site 948mentioning
confidence: 96%
“…Reorientation of the AMS axes in the prism domain (420−490 mbsf) offers a clearer picture of their significance. The reoriented k min axes are mostly subhorizontal and east-west trending, matching the convergence direction of N78°E (Deng and Sykes, 1995); the reoriented k max axes have north-south declinations and are subhorizontal (Fig. 7A).…”
Section: Site 948mentioning
confidence: 99%